European office markets, user costs and speculative bubbles - Michael Voigtländer; Florian Schuster (Institut der deutschen Wirtschaft (IW), 2019)
Over the last years, prices for European office space have reached new peaks. This naturally provokes discussion about a possible overheating in the market. One approach to assess price development of real estate markets is the so-called "user cost approach". Typically, this approach is applied to housing markets, but it can also be applied to commercial markets. The model follows the idea of no-arbitrage. If one kind of tenure is economically more attractive than another, households or corporates will shift demand, so that both tenures - buying and renting - should equalise over time. Thus, major differences between buying and renting indicate a possible over- or undervaluation of properties. In this contribution, user costs for offices have been calculated for 18 European capitals. The results indicate that in most European office markets, further price appreciations are likely. In Paris, Helsinki, Prague, Berlin, Stockholm, Amsterdam, Oslo and Luxembourg in particular, huge gaps between prime rents and user costs indicate further price increases, whereas in Madrid, Lisbon, Rome, London and Budapest further price decreases seem plausible. However, these likely price decreases do not follow the typical pattern of a correction of a speculative bubble, but are more or less the result of falling prime rents that have not been fully captured in prices, yet. The user cost approach has some predictive power, but can only provide an initial pointer towards under- or overvaluations. For instance, structural breaks such as Brexit can change long-term expectations, which cannot be captured properly in a model. However, the approach appears valuable in providing a first assessment. In future, the German Economic Institute will do further research on this topic in order to strengthen its understanding of commercial property markets.
Keywords: G12; O52; R33; 330